ANALISIS PENGAWASAN DAN PEMBINAAN HYGIENE SANITASI PANGAN (HSP) DI RUMAH MAKAN WILAYAH KERJA DINAS KESEHATAN ACEH BARAT DAYA - Wilda tun Nahri; Darmawan Darmawan; Yulizar Yulizar; Yarmaliza Yarmaliza; T Alamsyah (PT.Mantaya Idea Batara, 2025)
The implementation of the food hygiene and sanitation supervision and coaching program is a requirement for quality standards for health, safety and the feasibility of the place of management that must be carried out by every restaurant business actor. The purpose of the research is to find out how effective the implementation of the sanitation supervision and coaching program in restaurants. The research method uses qualitative research, data is obtained from the results of observation and in-depth interviews. The number of informants was eight. The research was carried out from January to February 2024. The resultsof the study show that the supervision and guidance program for restaurant hygiene and sanitation in the Southwest Aceh Health Office Work Area is carried out by a team in the Environmental Health Sector. The inhibiting factors in the implementation of the program are the unavailability of human resources, lack of budget, lack of infrastructure, implementation methods only using questionnaires, implementation strategies have not shown the success rate of restaurant businesses to obtain HSP worthiness certificates and there are no local government policies regulating intensive supervision and coaching. The conclusion of this study is that the problems of human resources, fund allocation, infrastructure, methods, strategies and policies show that there are still many challenges to be overcome.